Effective Fiscal Management in Higher Education: Factors For Success - Figer-Canes, Ryzel Maureen T. (PT. Antis International Publisher, 2024)
This research aimed to identify the factors that contribute to effective fiscal management in higher education institutions. The study used a mixed-methods approach, including surveys, focus group discussions, and document analysis, to collect data from six state universities and colleges in Eastern Visayas, Philippines. The results showed that the institutions have very satisfactory levels of compliance in their budget planning and preparation, disbursement, and liquidation processes. The factors that contribute to effective fiscal management include strict adherence to accounting rules and regulations, equitable allocation of resources, proper documentation, and the involvement of different school officials in the strategic development planning process. The study also revealed some challenges, including the lack of funding for certain priority projects and the need for better training and capacity-building for financial management personnel. The findings of this research can help higher education institutions in developing effective fiscal management strategies and policies that can lead to better financial performance and accountability.